2007
DOI: 10.1148/radiol.2421031988
|View full text |Cite
|
Sign up to set email alerts
|

Underestimation of the Presence of Breast Carcinoma in Papillary Lesions Initially Diagnosed at Core-Needle Biopsy

Abstract: Benign papilloma diagnosed at core biopsy is infrequently (3%) associated with malignancy; mammographic follow-up is reasonable. Because of the high association with malignancy (67%), diagnosis of atypical papilloma at core biopsy should prompt excision for definitive diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
118
5
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(133 citation statements)
references
References 15 publications
5
118
5
2
Order By: Relevance
“…The location of the papillary lesion is another widely studied risk factor. Some studies reported a tendency for the papillary lesion to be malignant if it was located at the periphery of the breast (19,20), whereas no such association was found in many other studies, including the present study (3,6,8).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The location of the papillary lesion is another widely studied risk factor. Some studies reported a tendency for the papillary lesion to be malignant if it was located at the periphery of the breast (19,20), whereas no such association was found in many other studies, including the present study (3,6,8).…”
Section: Discussioncontrasting
confidence: 80%
“…Reported upgrading rates from benign papillary lesions diagnosed by CNB to malignant papillary lesions diagnosed on subsequent surgical excision range from 0% to 29% (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Some investigators have suggested that benign papillary lesions without atypia diagnosed by CNB, in combination with concordant imaging findings, can be safely followed without further surgery (2-7).…”
mentioning
confidence: 99%
“…However, papillary lesions associated with epithelial atypia require surgical excision for definitive diagnosis because histologic underestimation occurs at a frequency similar to that in other atypical lesions undergoing NCB. 31,32,34,35 Although only one lesion diagnosed as cellular fibroepithelial lesion on core was malignant on excision, 36.5% were phyllodes tumors.…”
mentioning
confidence: 99%
“…So, when a definitive diagnosis of malignancy cannot be done because of discordant findings, sampling limitations of a core biopsy 5 or open biopsy, or limited sensibility of breast images, 5,6 resection of the entire lesion is mandatory [1][2][3][4]6 due to high association with malignancy. 1,2,4 The open biopsy was an attempt to improve the pathological results that were hindered by limitation of diagnostic procedures and discordant findings. Also, the indication for diagnostic mastectomy, 7 as seen in this case, is a fact that must be thoroughly discussed with the patient.…”
mentioning
confidence: 99%